2021
DOI: 10.3389/fimmu.2021.722581
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Regulates Exosome Release in Cultured Astrocytes

Abstract: Exosomes are vesicles secreted by various kinds of cells, and they are rich in cholesterol, sphingomyelin (SM), phosphatidylcholine, and phosphatidylserine. Although cellular sphingolipid-mediated exosome release has been reported, the involvement of other lipid components of cell membranes in the regulation of exosome release is poorly understood. Here, we show that the level of exosome release into conditioned media is significantly reduced in cultured astrocytes prepared from apolipoprotein E (ApoE) knock-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…Cholesterol-induced downregulation of ILV formation supports a previous report that cholesterol suppresses EV secretion in vivo. 32) We observed that SNAP23 expression level in pancreatic cancer is inversely correlated with that of sterol regulatory element-binding protein 1 (SREBP1), which promotes choles-terol synthesis 33) in the TCG A dataset (data not shown). The expression of SNAP23 reportedly decreased cholesterol and increased membrane fluidity in rat vascular smooth muscle cells (VSMCs).…”
Section: Discussionmentioning
confidence: 91%
“…Cholesterol-induced downregulation of ILV formation supports a previous report that cholesterol suppresses EV secretion in vivo. 32) We observed that SNAP23 expression level in pancreatic cancer is inversely correlated with that of sterol regulatory element-binding protein 1 (SREBP1), which promotes choles-terol synthesis 33) in the TCG A dataset (data not shown). The expression of SNAP23 reportedly decreased cholesterol and increased membrane fluidity in rat vascular smooth muscle cells (VSMCs).…”
Section: Discussionmentioning
confidence: 91%
“…In addition to Aβ15-33 WT , we synthetized Aβ15-33 K28A , Aβ15-33 E22K , and Aβ15-33 S26A peptides. We then assessed binding of these synthetic peptides to exosomes known to have membranes enriched in cholesterol playing a crucial role in the formation and release of exosomes [ 30 , 31 ]. Exosomes secreted by untransfected HEK293T cells were purified by ultracentrifugation and incubated with the three peptides for 1 h at 37 °C.…”
Section: Resultsmentioning
confidence: 99%
“…( 25 , 26 ), which provide anchoring sites for membrane proteins, encapsulate cargo in a separate space, and enable exosomal activity through fusion and separation. In astrocytes cholesterol was found to regulate exosome release through stimulation of the PI3K/Akt signaling pathway ( 27 ). Qi et al.…”
Section: Exosome Biologymentioning
confidence: 99%